New insights into the molecular dynamics of P3HT:PCBM bulk heterojunction: a time-of-flight quasi-elastic neutron scattering study - Guilbert,AA; Zbiri,M; Jenart,MV; Nielsen,CB; Nelson,J (Journal of Physical Chemistry Letters, 2016)
The molecular dynamics of organic semiconductor blend layers are likely to affect the optoelectronic properties and the performance of devices such as solar cells. We study the dynamics (5-50 ps) of the poly(3-hexylthiophene) (P3HT): phenyl-C61-butyric acid methyl ester (PCBM) blend by time-of-flight quasi-elastic neutron scattering, at temperatures in the range 250-360 K, thus spanning the glass transition temperature region of the polymer and the operation temperature of an OPV device. The behavior of the QENS signal provides evidence for the vitrification of P3HT upon blending, especially above the glass transition temperature, and the plasticization of PCBM by P3HT, both dynamics occurring on the picosecond time scale.